Growth Options and Related Stock Market Anomalies: Profitability, Distress, Lotteryness, and Volatility - Bali, Turan G.; Del Viva, Luca; Lambertides, Neophytos; Trigeorgis, Lenos (My University, 2020)
We provide new evidence about the economic role of growth options behind the profitability, distress, lotteryness, and volatility anomalies. We use idiosyncratic skewness to measure growth options and estimate expected idiosyncratic skewness capturing investors' expectation about the firm's mix of growth options versus assets-in-place. We find that investors require a positive premium to hold stocks of inflexible firms with low growth options and negative expected skewness, and that a newly proposed skewness factor based on growth options explains the aforementioned anomalies. Thus, the new measure of expected idiosyncratic skewness may serve to reduce the number of anomalies in the literature.
Keywords: Link; Crosssectional relations; Profitability; Distress risk; Lotteryness; Idiosyncratic skewness; Volatility